1994
DOI: 10.1212/wnl.44.5.978
|View full text |Cite
|
Sign up to set email alerts
|

Anosognosia and the intracarotid amobarbital procedure (Wada test)

Abstract: Microsomal triglyceride transfer protein (MTP)is an intraluminal protein in the endoplasmic reticulum (ER) that is essential for the assembly of apolipoprotein B (apoB)-containing lipoproteins. In this study, we examine how the livers of mice respond to two distinct methods of blocking MTP function: Cre -mediated disruption of the gene for MTP and chemical inhibition of MTP activity. Blocking MTP significantly reduced plasma levels of triglycerides, cholesterol, and apoB-containing lipoproteins in both wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…A subsequent study failed to replicate our findings (Dywan, McGlone, & Fox, 1995); however, other studies were able to replicate these findings (Carpenter et al, 1995;Durkin, Meador, Nichols, Lee, & Loring, 1994). The reason why Dywan et al's study did not replicate our study is not known, but occasionally we do observe patients who with left hemisphere anesthesia were not aware of their weakness and other patients who are aware of their weakness after right hemisphere anesthesia.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 61%
“…A subsequent study failed to replicate our findings (Dywan, McGlone, & Fox, 1995); however, other studies were able to replicate these findings (Carpenter et al, 1995;Durkin, Meador, Nichols, Lee, & Loring, 1994). The reason why Dywan et al's study did not replicate our study is not known, but occasionally we do observe patients who with left hemisphere anesthesia were not aware of their weakness and other patients who are aware of their weakness after right hemisphere anesthesia.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 61%
“…Despite a trend toward a higher frequency of anosognosia following suppression of right hemisphere activity, presence of unawareness following suppression of left hemisphere activity ranged from 49% (Breier et al, 1995) to 86% (Durkin, Meador, Nichols, Lee, & Loring, 1994). …”
mentioning
confidence: 83%
“…Studies using the Wada test that were carried out with a large group of volunteers (e.g., Dywan, McGlone, & Fox, 1995) showed a different pattern of results (see Table 1). Despite a trend toward a higher frequency of anosognosia following suppression of right hemisphere activity, presence of unawareness following suppression of left hemisphere activity ranged from 49% (Breier et al, 1995) to 86% (Durkin, Meador, Nichols, Lee, & Loring, 1994).…”
mentioning
confidence: 83%
“…This is a clear limitation in studies attempting to assess anosognosia in aphasic patients, and has led to high exclusion rates of left brain damaged patients, and possible underestimation of anosognosia for right hemiplegia (e.g., Cutting, 1978;Morin et al, 2007;Cocchini et al, 2009). Studies capi talising on the intra-carotid sodium amobarbital procedure (Wada test) did show a higher frequency of anosognosia for left hemiplegia after anesthesia of the right hemisphere; however, they also indicated that when the left hemisphere was inactivated, the frequency of anosognosia for right hemiplegia varied greatly, ranging from zero (Gilmore et al, 1992) to 86% (Durkin et al, 1994). It follows that the apparent strong hemispheric asymmetry that has guided research and theoretical interpretations may suffer from a methodological bias, and the left hemisphere may play some role in awareness, even if probably less crucial than or different from that of the right hemisphere.…”
Section: Anosognosia For Motor Impairmentsmentioning
confidence: 99%